Evidence of a cloud-cloud collision from overshooting gas in the galactic center - Gramze, Savannah R.; Ginsburg, Adam; Meier, David S.; Ott, Jürgen; Shirley, Yancy; Sormani, Mattia C.; Svoboda, Brian E. (The astrophysical journal, 2023)
The Milky Way is a barred spiral galaxy with bar lanes that bring gas toward the Galactic center. Gas flowing along these bar lanes often overshoots, and instead of accreting onto the Central Molecular Zone (CMZ), it collides with the bar lane on the opposite side of the Galaxy. We observed G5, a cloud that we believe is the site of one such collision, near the Galactic center at (ℓ, b) = ( +5.4, −0.4) with the Atacama Large Millimeter/submillimeter Array/Atacama Compact Array. We took measurements of the spectral lines 12CO J = 2 → 1, 13CO J = 2 → 1, C18O J = 2 → 1, H2CO J = 303 → 202, H2CO J = 322 → 221, CH3OH J = 422 → 312, OCS J = 18 → 17, and SiO J = 5 → 4. We observed a velocity bridge between two clouds at ∼50 and ∼150 km s−1 in our position-velocity diagram, which is direct evidence of a cloud-cloud collision. We measured an average gas temperature of ∼60 K in G5 using H2CO integrated-intensity line ratios. We observed that the 12C/13C ratio in G5 is consistent with optically thin, or at most marginally optically thick 12CO. We measured for the local XCO, 10-20× less than the average Galactic value. G5 is strong direct observational evidence of gas overshooting the CMZ and colliding with a bar lane on the opposite side of the Galactic center.